Analisis Minat Konsumen pada Warung Kopi di Kota Banda Aceh - Rahmat Fadhil; Sayed Mahdi; Fachruddin Fachruddin; Putra Bahrumi (Jurnal Ilmu Pertanian Indonesia, 2023)
The number of businesses like coffee shops (warkop) in Banda Aceh City makes every business actor required to implement the right strategy in capturing the hearts of consumers so that they can continue to visit that the company's income can increase. Therefore, this study aims to analyze consumer interest in choosing warkop in Banda Aceh City so that business actors can use the information obtained in making decisions to be applied to their business. The observation locations were carried out in five coffee shops. Based on the results of the study, several factors become a reference for consumers in choosing the warkop to visit, including location, place, price, internet, parking facilities, and mushalla. However, in some coffee shops, there are also problems in providing quality services, such as delays in the handling process, slight menu variations, the noise of places, parking lots, and less strategic locations. Thus, if the problem is not addressed properly, it is estimated that it can have an impact on the nature of the next consumer. With a soft systems methodology (SSM) approach, these problems can be overcome. SSM can build a conceptual model that can formulate a strategy for warkop business actors in Banda Aceh City. SSM method results in two suggested recommendation activities. First, technical recommendations, namely that business actors must make efforts in improving their companies, such as determining strategic locations, setting competitive prices, providing adequate parking space, and fixing various other factors. Second, policy recommendations include establishing special SOPs, developing human service resources, incorporating local wisdom, and innovating. So applying these two activity recommendations can provide answers to problems. Keywords: coffee shop, conceptual model, consumer interest, soft systems methodology